PKK, Potensi Pemanfaatan Keuangan Negara dan Neo-Ibuisme Negara di Sumatera Barat - M. Nurul Fajri; Muhammad Ichsan Kabullah (Badan Pengawas Pemilihan Umum, 2019)
This paper elaborate on the phenomenon of the wife of the regional head and deputy regional head in West Sumatra who are candidates for legislative members. These wives may directly or indirectly who have utilized the state’s budget and reflects appear the new state ibuism. This is inseparable from the weak side associated with campaign rules in realizing intergrity and fair election. There were eight wives of regional heads and deputy regional heads in West Sumatra advancing as candidates for legislative members in the 2019 elections. This has increased dramatically when looking at the 2014 elections where only one wife of regional heads advanced as candidates for legislative members. Despite having various electoral strategies, this phenomenon provides a dangerous signal for the use of state budget for electoral political interests. Nevertheless, the wife of the regional head is automatically become the Chairperson of the Family Empowerment and Welfare Movement (TP PKK) along with the wife of the deputy regional head. In the other hand, PKK is one of the instruments of institutionalizing the new state ibuism. In other words, the increasing trend in advancing the wife of the regional head and deputy regional head also requires adjustments to the rules regarding the campaign. Because, the state facilities or government programs delivered, like government advertising programs, are not allowed to use them for political campaign activities. Moreover, the phenomenon can be open our eyes that the new state ibuism which is facilitated by the loophole of the rule of law